Phenotypic and molecular study of carbapenem‑resistant enterobacteriaceae in a referral hospital in the East coast Malaysia - Yahya Mohsen, Saleh Mahdi; Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen (JSS University Sri Shivrathreeshwara Nagar, 2018)
Introduction: Infections due to carbapenemase‑producing Enterobacteriaceae have been increasingly reported worldwide and are causing significant health concerns. In this study, we investigated the occurrence of New Delhi Metallo‑beta‑lactamase (NDM) carbapenemase‑producing Enterobacteriaceae (CPE) in Enterobacteriaceae isolates from Hospital Tengku Ampuan Afzan (HTAA) and verified the presence of associated carbapenemases genes. MATERIALS AND METHODS: Standard antimicrobial susceptibility testing was performed to analyze the isolates’ susceptibility pattern. Modified Hodge test was used to detect carbapenemase production. Genes associated with CPE were detected by standard polymerase chain reaction amplification with a series of established primers, followed by DNA sequencing. RESULTS: Out of 259 Enterobacteriaceae isolates, four Klebsiella pneumoniae isolates (1.5%) were found to be phenotypically carbapenem‑resistant. NDM‑1 carbapenemase was detected in three of the four isolates. Two of them were recovered from blood and the third strain was isolated from a urine sample. The three isolates were found to be resistant to all β‑lactams antibiotics and the majority of other nonβ‑lactam antibiotics. Meanwhile, all the isolates were susceptible to polymyxin B. They also carried other β‑lactamase genes along with the blaNDM gene. Nucleotide sequence of the blaNDM‑1 gene showed no base variation with other NDM‑1 sequences from the NCBI nucleotide database. CONCLUSION: The presence of NDM‑producing K. pneumoniae in the HTAA is alarming and of serious concern due to the high‑level resistance of this gene and the risk of an outbreak occurrence. Further studies to detect the genetic relatedness and clonality of these resistance organisms are highly recommended.